2014
DOI: 10.1007/s00198-014-2919-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of stroke among hip fracture patients: a nationwide cohort study

Abstract: Hip fracture is independently associated with a subsequent risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
(33 reference statements)
2
15
1
Order By: Relevance
“…For symptomatic stroke, a registry‐based study from Taiwan reported an absolute risk of 4% within 1 year among 2101 hip fracture patients . A second study from this source estimated an incidence rate of 35 per 1000 person‐years among 6013 hip fracture patients during a mean follow‐up of 4 years . This was higher than the 1‐year risk of 2.18% estimated in our study.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…For symptomatic stroke, a registry‐based study from Taiwan reported an absolute risk of 4% within 1 year among 2101 hip fracture patients . A second study from this source estimated an incidence rate of 35 per 1000 person‐years among 6013 hip fracture patients during a mean follow‐up of 4 years . This was higher than the 1‐year risk of 2.18% estimated in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…Nevertheless, our relative risk estimates for stroke are generally consistent with the findings of these two studies. They observed a relative risk of 55% within 1 year and 46% during 5 years to a maximum of 12 years of follow‐up. We extended these findings by showing that risk of stroke persists up to 10 years following hip fracture, but not beyond this period—suggesting the need for targeting preventive treatment for stroke during and shortly after hospital admission to reduce stroke risk within 1 year, as well as for providing long‐term preventive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Within the first year of hip surgery, about 4% patients will suffer from stroke. Currently in the US, there are six million hip fractures/year, 6,8 that will increase with the population aging. As advanced age is a risk factor for both stroke and fracture, it is imperative to understand the neurobiologic underpinnings for the association of these two conditions on the trajectory of aged-related cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…The patients in the LHID2000 were diagnosed according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes. This database has been reliably used in our previous studies 17,18 . This cohort study was approved by the Institutional Review Board of Tsaotun Psychiatric Center.…”
Section: Data Sourcementioning
confidence: 99%